2014
DOI: 10.3174/ajnr.a4018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple Parameters Obtained on 3T Pulsed Arterial Spin-Labeling, Diffusion Tensor Imaging, and MRS and the Ki-67 Labeling Index in Evaluating Glioma Grading

Abstract: BACKGROUND AND PURPOSE:Pulsed arterial spin-labeling, DTI, and MR spectroscopy provide useful data for tumor evaluation. We evaluated multiple parameters by using these pulse sequences and the Ki-67 labeling index in newly diagnosed supratentorial gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 28 publications
(54 reference statements)
3
69
0
3
Order By: Relevance
“…Another interesting finding was that CBF max and rCBF max showed a dual relationship with the degree of malignancy in gliomas. In accordance with previous studies based on pulsed ASL and CASL, [8][9][10][11][12][13][14][15][16][17] both CBF max and rCBF max obtained from pCASL increased with increasing grade of gliomas, and gliomas with higher CBF max and rCBF max were associated with worse PFS. These findings suggest that gliomas with higher rCBF max are associated with a higher degree of malignancy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another interesting finding was that CBF max and rCBF max showed a dual relationship with the degree of malignancy in gliomas. In accordance with previous studies based on pulsed ASL and CASL, [8][9][10][11][12][13][14][15][16][17] both CBF max and rCBF max obtained from pCASL increased with increasing grade of gliomas, and gliomas with higher CBF max and rCBF max were associated with worse PFS. These findings suggest that gliomas with higher rCBF max are associated with a higher degree of malignancy.…”
Section: Discussionsupporting
confidence: 91%
“…8,9 Arterial spin-labeling (ASL) is a noninvasive MR perfusion imaging technique for obtaining CBF maps. Some previous studies based on pulsed ASL and continuous ASL (CASL) have shown that the ASL-derived CBF maps have potential value in grading gliomas 8,[10][11][12][13][14][15] and predicting their progression. 9,16,17 However, although pseudocontinuous ASL (pCASL) is considered an improved method over pulsed ASL and CASL, [18][19][20] a recent study reported that pCASL-derived CBF maps failed to accurately grade gliomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have argued that multiparametric MR imaging methods have the potential to improve the diagnostic performance of preoperative glioma grading. [30][31][32] Furthermore, Yoon et al 1 reported that adding FDG-PET to multiparametric MR imaging, including DWI, PWI, and MR spectroscopy, can improve the diagnostic accuracy of glioma grading. However, few studies have examined glioma grading with multiparametric imaging that included APT imaging and PWI or DWI.…”
Section: Additive Value Of Apt Imaging To Dwi For Glioma Gradingmentioning
confidence: 99%
“…Pulsed arterial spin-labeling and diffusion tensor imaging as additional method to MR spectroscopy seem to be very useful for predicting glioma grade [29].…”
Section: Astrocytoma II 18mentioning
confidence: 99%